2020
DOI: 10.1108/heswbl-08-2019-0106
|View full text |Cite
|
Sign up to set email alerts
|

Work integrated learning resources for students with disabilities: are post-secondary institutions in Canada supporting this demographic to be career ready?

Abstract: PurposeThe Government of Canada is adopting the pedagogical practice of Work Integrated Learning (WIL) to help youth develop the career ready skills needed to transition from school to work. As a result, colleges and universities are receiving funding to grow academic programs that link theoretical learning with practical work experience. However, there is limited research about the resources available to students with disabilities who engage in WIL. From an environmental scan of disability supports for WIL on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Noteworthy, it has been found that up to 75% of students do not disclose their disabilities due to fears about how they would be perceived and stigmatised and a concern over the course policies and procedures involved in that process of declaration (Dollinger et al, 2022). Similar findings have been found across the literature (Gatto et al, 2021;Moriña & Biagiotti, 2022;Nolan et al, 2015).…”
Section: Employability Challenges With a Disabilitysupporting
confidence: 70%
“…Noteworthy, it has been found that up to 75% of students do not disclose their disabilities due to fears about how they would be perceived and stigmatised and a concern over the course policies and procedures involved in that process of declaration (Dollinger et al, 2022). Similar findings have been found across the literature (Gatto et al, 2021;Moriña & Biagiotti, 2022;Nolan et al, 2015).…”
Section: Employability Challenges With a Disabilitysupporting
confidence: 70%
“…Such programmes have been very popular in the developed world but they seemed unpopular in Sub-Saharan Africa. Work integrated learning is already popularised by sectors in Canada and Europe and this is in some cases at the level of government (Gatto et al ., 2021; Rangraz and Pareto, 2021). Mugizi (2019) found that there was a gap between organisational commitment and employee training and development in many educational institutions in Wakiso district of Uganda.…”
Section: The Case Of Ugandamentioning
confidence: 99%
“…Therefore, in the academic context, there has been an increase in programmes to promote the integration of persons with disabilities into the labour market (Gatto et al, 2021). In this sense, the aim is to provide students with useful resources to successfully overcome the obstacles they may find in the world of work.…”
Section: Universities: Key Pieces To the Transition To Employmentmentioning
confidence: 99%